A esfera pública política no pensamento de Jürgen Habermas: problemas, limites e perspectivas - Almeida, Paulo Roberto Andrade de (2018)
The goal of this thesis is to present the evolution of the concept of political public sphere, in the thought of the German philosopher Jürgen Habermas. The author had accused the Decline of the bourgeois liberal public sphere, corrupted by Power, in concluding his work Strukturwandel der Öffentlichkeit and pursued the theme throughout his academic-editorial career. Therefore, it is opportune to ask: how to revitalize (or repolitize) the public sphere? We believe that the decisive step in facing this aporia is the replacement of the metaphor of besieging by the metaphor of locks, in a new model of circulation of power, which would be referred to in Faktizität und Geltung. Our research has bibliographical character and aims to demonstrate how the author overcomes the historical and sociological conditions present in his initial conception of the public sphere and, using the philosophy of language, Luhmann's theory of systems and dialoguing with several intellectuals, inaugurates a new apprehension of society, as system and world of life. The pragmatic use of language contributes to the formation of the will and opinion of individuals, who intervene in the parliamentary complex, determining the direction of their decisions. This is what he calls deliberative democracy, a procedure legitimized by law.